Agroecosystem diversity reconciling contemporary agriculture and environmental quality - Lemaire, Gilles 1945-; De Faccio Carvalho, Paulo César; Kronberg, Scott; Recous, Sylvie (Academic Press, 2019)
Agro-Ecosystem Diversity: Impact on Food Security and Environmental Quality presents cutting-edge exploration of developing novel farming systems and introduces landscape ecology to agronomy. It encompasses the broad range of links between agricultural development and ecological impact and how to limit the potential negative results. Presented in seven sections, each focusing on a specific challenge to sustaining diversity, the book provides insights toward the argument that by re-introducing diversity, it should be possible to maintain a high level of productivity of agro-ecosystems while also maintaining and/or restoring a satisfactory level of environment quality and biodiversity